Plant Adaptation and Phytoremediation 2010
DOI: 10.1007/978-90-481-9370-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Toxicity in Plants

Abstract: Although many metal elements are essential for the growth of plants in low concentrations, their excessive amounts in soil above threshold values can result in toxicity. This detrimental effect varies with the nature of an element as well as plant species. Heavy metal toxicity in plants depends on the bioavailability of these elements in soil solution, which is a function of pH, organic matter and cation exchange capacity of the soil. Nonessential metals/metalloids such as Hg, Cd, Cr, Pb, As, and Sb are toxic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
1
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 179 publications
(171 reference statements)
0
46
1
9
Order By: Relevance
“…They found that roots were inhibited by 70%, while shoots were reduced only by 50% in the presence of Zn.The inhibition of roots and shoots elongation caused by heavy metals can be due to their influence on cell division (Davies et al, 1991;Hargemeyer, Breckle, 1996), or their effect on cell wall elasticity and metabolic activities (Naseer et al, 2001). As we know, roots are the first part of the plant that comes in touch with contamination, they are more sensitive to toxicity by metals than shoots (Araujo, Monteiro, 2005;Shah et al, 2010;Yang et al, 2010;Yusuf et al, 2011). This sensibility reduced per consequence of the root/shoot ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that roots were inhibited by 70%, while shoots were reduced only by 50% in the presence of Zn.The inhibition of roots and shoots elongation caused by heavy metals can be due to their influence on cell division (Davies et al, 1991;Hargemeyer, Breckle, 1996), or their effect on cell wall elasticity and metabolic activities (Naseer et al, 2001). As we know, roots are the first part of the plant that comes in touch with contamination, they are more sensitive to toxicity by metals than shoots (Araujo, Monteiro, 2005;Shah et al, 2010;Yang et al, 2010;Yusuf et al, 2011). This sensibility reduced per consequence of the root/shoot ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Heavy metals have been shown to affect different processes of plant functions, and clearly have a negative impact on seed germination. They can engender damage to the root system of plants (Singh, Thakur, 2014), by causing an oxidative stress by producing free radicals (Shah et al, 2010), or by replacing nutrient and essential metals (Henry, 2000). In general, the influence of trace elements on plants depends mainly on the heavy metal kind, the concentration applied and plant species.…”
Section: Introductionmentioning
confidence: 99%
“…Siendo la alfalfa una planta considerada como acumuladora de metales pesados, hace suponer un riesgo de contaminación por la ingestión que de ella realizan los animales (45) . Algunos metales como el Co, Mn, Fe, Se, Zn, Cu y Ni, son esenciales para las funciones biológicas y fisiológicas de plantas, incluyendo la biosíntesis de proteínas, ácidos nucleicos, sustancias de crecimiento, síntesis de clorofila entre otras funciones; pero más allá de los límites permisibles, estos elementos metálicos se vuelven tóxicos dependiendo de la naturaleza, especies de metal y plantas (46) .…”
Section: Figuraunclassified
“…The well evidenced Cd toxicity in rice plants is the implement of oxidative stress and the production of lipid peroxidation (Shah et al, 2001). Moreover, Cd influences the uptake, transport and use of necessary elements in plants, such as Fe, Zn, Mn and Cu (Rehman Shah et al, 2010). Cadmium has also negative impact on light harvesting centre and photosystem II, as well as chlorophyll metabolism in rice leaves (Pagliano et al, 2006).…”
Section: Cadmium In Rice Fieldmentioning
confidence: 99%